If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(5x + -6) + -12 = -2(9s + 4) + -3 Reorder the terms: -2(-6 + 5x) + -12 = -2(9s + 4) + -3 (-6 * -2 + 5x * -2) + -12 = -2(9s + 4) + -3 (12 + -10x) + -12 = -2(9s + 4) + -3 Reorder the terms: 12 + -12 + -10x = -2(9s + 4) + -3 Combine like terms: 12 + -12 = 0 0 + -10x = -2(9s + 4) + -3 -10x = -2(9s + 4) + -3 Reorder the terms: -10x = -2(4 + 9s) + -3 -10x = (4 * -2 + 9s * -2) + -3 -10x = (-8 + -18s) + -3 Reorder the terms: -10x = -8 + -3 + -18s Combine like terms: -8 + -3 = -11 -10x = -11 + -18s Solving -10x = -11 + -18s Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '-10'. x = 1.1 + 1.8s Simplifying x = 1.1 + 1.8s
| b+b2+b/6=190 | | 4*x^3+5*x^2+x=1 | | -10m-4=4-10m | | (4+8x)/(2x+1) | | 180=6000*.12*t | | 4(5x-1)-4=14x-2 | | 5(3x+1)=2(5x-4)+6x | | 27(1.4+1.2)-26(1.4+1.2)= | | -65.375=7.2(9c+1) | | (2x+9)+(2x+8)+(2x)=(2x)+(3x+1) | | 2a/3+1/5 | | 7/3x+9/6x=36/9 | | 10y=12.6 | | -3a+4=-8 | | 6(3x-2)=18x-12 | | 4x^2+19x+22=0 | | 35=45 | | (-2/7)(2m+6)=(1/28)m-11 | | x+15+2x=-5-2x-30 | | -14-4(x)=-58 | | 6(2x+6)= | | 8y+3(y-5)=6(y+1)-3 | | 40/x-40x+39=0 | | 2(3x-6)+5=12-(x+5) | | r-3/7r=98000 | | (8x^2-3x^3)-(5x^2-9x^3)= | | 4556776+455556= | | 4.2+10m=6.75 | | (1/4)d-(2/5)=(3/4)d+11 | | 10=a-7 | | x^2-(6x)=13 | | 7x+2x(x+6)=39 |